Konsep Desain Kopi Combre Untuk Industri Skala Mikro - Saepuddin, Ahmad; Permadi, Luchyto Chandra; Adiwibowo, Priyo Heru; Kurniawan, Wahyu Dwi; Nurjannah, Ika; Drastiawati, Novi Sukma; Fitriani, Indah Martha; Yunitasari, Bellina; Hidayatullah, Rachmad Syarifudin (Riau Journal of Empowerment, 2024)
One of the challenges faced by micro-businesses like Kopi Combre in the village of Sumberdem, Wonosari District, when they want to use packaging for their products is selecting packaging that is unique and appealing to consumers. The primary goal of this community engagement project is to provide guidance in designing packaging structures and labels suitable for the micro-scale industry, particularly for Kopi Combre. The method involves community engagement and incorporates literature studies and information analysis. This study covers aspects such as coffee product attributes, packaging structure design, and labels. The findings indicate that the most suitable packaging type for the micro-scale industry is the Pouch packaging, while the packaging and label design will feature dark colors and include information about the coffee product and a unique brand.